Sifat Eskatologis Gereja Kalimantan Timur dalam Gerakan Kerajaan Allah - Fabianus Sidi (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2020)
The main mission of Christ is to proclaim the kingdom of God. The church that follows Jesus Christ continues Christ's mission, which is to proclaim the Kingdom of God. Church life in the movement of the kingdom of God contains futurist and presentist eschatological values. The Church has many dimensions with different understandings of the eschatological character of the Church. In accordance with the vision of the East Kalimantan Church of the Archdiocese of Samarinda, namely the Church following Jesus Christ presents the Kingdom of God both outwardly and inwardly '' with the pressure of the Church's outward movement, it can be concluded that the East Kalimantan Church adheres to the Church model as a servant or servant. The church is called to uphold justice and foster brotherhood in this world and it will be perfected in the kingdom of God.